(untitled) (Journal of Medical & Health Sciences Review, 2026)
This article examines the limitations of current quality evaluation systems in radiology, which often focus on operational metrics rather than patient outcomes. It highlights the need for a comprehensive approach that incorporates diagnostic accuracy, clinical impact, and patient-centered perspectives. The article advocates for value-based healthcare models that better recognize radiology’s role in improving patient care. It suggests integrating outcome-based indicators and using AI-driven analytics to enhance real-time feedback and quality improvement in radiology departments, aligning with the broader trend toward value-based care focused on accurate diagnoses and improved patient outcomes.